Remission of Hypertension Through Lifestyle Modification: A Case Study - Yunus, Nor Akma; Ng, Ying Ying (IIUM Medical Journal Malaysia, 2025)
Hypertension is a common comorbidity associated with obesity, and weight reduction offers numerous health benefits, including improved blood pressure control. This case study presents a 38-year-old man with an initial body mass index (BMI) of 35.5 kg/m2 who achieved hypertension remission through comprehensive lifestyle modifications. A structured program incorporating dietary changes, regular physical activity, and behavioral therapy led to a sustained BMI reduction to 25.8 kg/m². This weight loss was accompanied by a gradual normalization of blood pressure, allowing for the discontinuation of three antihypertensive medications irbesartan, hydrochlorothiazide, and amlodipine after approximately one year of lifestyle modification. Remarkably, his blood pressure remained within the normal range for three years following medication cessation, which was maintained through continued adherence to lifestyle interventions.